2015
DOI: 10.3389/fncel.2015.00301
|View full text |Cite
|
Sign up to set email alerts
|

Maternal immune activation evoked by polyinosinic:polycytidylic acid does not evoke microglial cell activation in the embryo

Abstract: Several studies have indicated that inflammation during pregnancy increases the risk for the development of neuropsychiatric disorders in the offspring. Morphological brain abnormalities combined with deviations in the inflammatory status of the brain can be observed in patients of both autism and schizophrenia. It was shown that acute infection can induce changes in maternal cytokine levels which in turn are suggested to affect fetal brain development and increase the risk on the development of neuropsychiatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 69 publications
7
56
2
Order By: Relevance
“…In our model, an indication of excessive neural progenitor cell phagocytosis was evident in the decreased estimated hippocampal neuronal cell density in MIA piglets, while microglial overactivation (measured by MHCII expression) was not apparent. A lack of microglial activation aligns with previous studies [30, 79-81], though we acknowledge that lasting microglial activation in this model cannot be ruled out solely by MHCII expression. Though MHCII is a widely used marker of classic microglial activation, microglia continuously take on varying states of activation that do not necessarily fall into classic or alternative categorizations [82-84] and resting or quiescent microglia still actively survey their environment and can engulf and clear parenchymal debris [85].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In our model, an indication of excessive neural progenitor cell phagocytosis was evident in the decreased estimated hippocampal neuronal cell density in MIA piglets, while microglial overactivation (measured by MHCII expression) was not apparent. A lack of microglial activation aligns with previous studies [30, 79-81], though we acknowledge that lasting microglial activation in this model cannot be ruled out solely by MHCII expression. Though MHCII is a widely used marker of classic microglial activation, microglia continuously take on varying states of activation that do not necessarily fall into classic or alternative categorizations [82-84] and resting or quiescent microglia still actively survey their environment and can engulf and clear parenchymal debris [85].…”
Section: Discussionsupporting
confidence: 65%
“…Microglia begin colonizing the brain during early gestation [24, 25] and aid in healthy neurodevelopment by producing neurotrophic factors and by phagocytosing excess cells and synapses [24-29]. Currently, studies determining the role of fetal microglia in MIA are conflicting; though Cunningham et al [24] demonstrated that activated microglia in a maternal LPS model deplete the fetal neural progenitor pool by excessive phagocytosis, Smolders et al [30] failed to find any activation of fetal microglia due to maternal poly I:C treatment at embryonic day (E) 11.5 or double injection at E11.5 and E15.5. Pratt et al [31], however, demonstrated that the same dose of poly I:C administered at E12.5 resulted in an increased production of several proinflammatory cytokines and chemokines by fetal microglia, while the total number of microglia was unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…While these data suggest that some aspect of microglia respond in a lasting way to early-life insult, the literature is mixed with regard to the longevity and magnitude of these changes (Smolders et al, 2015; Antonson et al, 2016; Giovanoli et al, 2016). Additionally, there are only a few studies that address how embryonic microglia morphology reflects their function.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study using the same poly(I:C)--based immune activation model in mice showed that there were no significant differences in fetal microglial cell density or activation levels between offspring of immune--stimulated and control mothers (Smolders et al, 2015). Our interpretations are consistent with these findings and generally question a major involvement of microglia--driven processes in precipitating short--and long--term The line plot shows percent prepulse inhibition (%PPI) as a function of the 3 distinct pulse levels (P--100, P--110 and P--120, which correspond to 100, 110 and 120 dBA) and prepulse levels (+6, +12 and +18 dBA above background of 65 dBA) for pubescent and adult offspring of poly(I:C)--exposed (POL) and control (CON) mothers, and the bar plot depicts the mean %PPI across all prepulse and pulse stimuli used.…”
mentioning
confidence: 98%